FACTORS RELATED TO WORK FATIGUE IN OCBC TOWER CONSTRUCTION PROJECT FINISHING WORKERS AT PT BUANAMAJU HASTASENTOSA IN 2024 - Banny Adam; Januar Ariyanto; Dihartawan; Luqman Effendi (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Work fatigue is a problem in the field of Occupational Health and safety that can be one of the factors in workplace accidents. In 2018, there were 173,105 cases in the management and construction industry. With one of the factors causing the occurrence is the condition of fatigue at work. In 2013, and 65% of the workforce experienced physical fatigue. This study aims to determine the factors associated with work fatigue at PT Buanamaju Hastasentosa workers where finishing work is done at night because it is done when employees go home from work and many construction workers are overtime because the work has not been completed. The population of this study is all workers of PT Buanamaju Hastasentosa as many as 60 workers who work in the finishing project OCBC tower South Jakarta. Data analysis of this study using the chi square assay α =0.05. The results showed that workers who experience severe fatigue there are 24 (40%) workers there and the calculation of the bivairiat test obtained age (p-value=0.023), smoking status (p-vaue=0.035), sleep quality (p-value=0.027), between periods of work (p-value=0.087). Conclusion in this study there is a relationship between age, smoking status and sleep quality with work fatigue and there is no relationship between the length of work with work fatigue. The author's suggestion is that there are still workers who experience severe fatigue, to reduce fatigue, the company can provide training to prevent work fatigue.